Losartan attenuates paraquat-induced pulmonary fibrosis in rats. (May 2015) - Guo, F; Sun, YB; Su, L; Li, S; Liu, ZF; Li, J; Hu, XT; Li, J
Paraquat (PQ) is one of the most widely used herbicides in the world and can cause pulmonary fibrosis in the cases with intoxication. Losartan, an angiotensin II type 1 receptor antagonist, has beneficial effects on the treatment of fibrosis. The aim of this study was to examine the effect of losartan on pulmonary fibrosis in PQ-intoxicated rats. Adult male Sprague Dawley rats ( n = 32, 180–220 g) were randomly assigned to four groups: (i) control group; (ii) PQ group; (iii) PQ + losartan 7d group; and (iv) PQ + losartan 14d group. Losartan treatment (intragastrically (i.g.), 10 mg/kg) was performed for 7 and 14 days after a single i.g. dose of 40 mg/kg PQ. All rats were killed on the 16th day, and hematoxylin–eosin and Masson's trichrome staining were used to examine lung injury and fibrosis. The levels of hydroxyproline and transforming growth factor β1 (TGF-β1), matrix metallopeptidase 9 (Mmp9), and tissue inhibitor of metalloproteinase 1 (TIMP-1) messenger RNA (mRNA) expression and relative expression levels of collagen type I and III were also detected. PQ caused a significant increase in hydroxyproline content, mRNA expression of TGF-β1, Mmp9, and TIMP-1, and relative expression levels of collagen type I and III ( p < 0.05), while losartan significantly decreased the amount of hydroxyproline and downregulated TGF-β1, Mmp9, and TIMP-1 mRNA and collagen type I and III expressions ( p < 0.05). Histological examination of PQ-treated rats showed lung injury and widespread inflammatory cell infiltration in the alveolar space and pulmonary fibrosis, while losartan could markedly reduce such damage and prevent pulmonary fibrosis. The results of this study indicated that losartan could reduce lung damage and prevent pulmonary fibrosis induced by PQ.